+0  
 
0
45
3
avatar+189 

\((-2)^4 - 2^4 + (-3)^3 - 3^3\)

Compute this please

 

Thanks!

 May 2, 2020
 #1
avatar+657 
+1

\(\begin{align*} (-2)^4 &= (-2)(-2)(-2)(-2) = 16,\\ 2^4 &= 2\cdot 2\cdot 2\cdot 2 = 16,\\ (-3)^3&= (-3)(-3)(-3) = (9)(-3) = -27,\\ 3^3 &= 3\cdot3\cdot3 = 27, \end{align*}\)

 

\([(-2)^4 -2^4 + (-3)^3 - 3^3 = 16-16 -27-27 = \boxed{-54} \)

 

coolsmileycool

 May 2, 2020
 #2
avatar+189 
+1

Thanks!

Your the best LuckyDucky!!! smiley

SoggyPerson  May 2, 2020
 #3
avatar+657 
+1

Of course!

 

coolsmileycool

LuckyDucky  May 2, 2020

39 Online Users

avatar
avatar
avatar
avatar
avatar
avatar